High-gain bidirectional Er3+-doped fiber amplifier for conventional- and long-wavelength bands - Mahdi, M.A.; Adikan, Faisal Rafiq Mahamd; Poopalan, P.; Selvakennedy, S.; Ahmad, Harith (Institute of Electrical and Electronics Engineers (IEEE), 2000)
High average gains of greater than 31 dB have been obtained between 1530-1560 nm (conventional-wavelength band, C-band) and 1570-1600 nm (long-wavelength band, L-band) using a saturating tone technique that represents 64 channels of a wavelength division multiplexed system. A bidirectional amplifying stage is utilized as high-power C-band and low-noise L-band stages. Noise figures of less than 3.6 and 5.4 dB are measured for the C- and L-bands, respectively.